VD_FINDINFO Jug / 2011 / 200 vom 27. Juli 2011 - VD Tribunal cantonal (2011)
PRESCRIPTION, ACTION PÉNALE, CRÉANCE, PRÉTENTION DE DROIT PUBLIC, DOL ÉVENTUEL | 109 CP, 12 al. 2 CP, 144 al. 1 CP, 144 CP, 71 al. 1 CP